FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PINJAMAN ONLINE DI INDONESIA - Leong, Eufranto Dedy Yulianto; Nirmala, Tiara (Yayasan Education and Social Center, 2024)
Financial Technology (fintech) is one of the financial service institutions that is currently in great demand, especially in terms of money loans or what is known as Financial Technology peer to peer lending (Online Loans). Due to the easy conditions and without the need for face-to-face meetings, certain groups of people use online loans as an alternative or solution to solving their financial problems. The aim of this research is to determine the factors that cause people to easily choose or decide to use online loans. The research method used by the author is a qualitative method through a more in-depth study of published sources such as journals, books, reports and articles as well as online sources. The results of this research show three main factors that influence the level of online loan use in Indonesia: consumer behavior driven by digital technology and easy access to financial services; low financial literacy which causes a lack of risk understanding; and uneven financial inclusion, limiting access to information about formal financial services